Regulation of nuclear transcription by mitochondrial RNA in endothelial cells - Kiran Sriram; Zhijie Qi; Dongqiang Yuan; Naseeb Kaur Malhi; Xuejing Liu; Riccardo Calandrelli; Yingjun Luo; Alonso Tapia; Shengyan Jin; Ji Shi; Martha Salas; Runrui Dang; et al. (eLife, 2024)
Chromatin-associated RNAs (caRNAs) form a relatively poorly recognized layer of the epigenome. The caRNAs reported to date are transcribed from the nuclear genome. Here, leveraging a recently developed assay for detection of caRNAs and their genomic association, we report that mitochondrial RNAs (mtRNAs) are attached to the nuclear genome and constitute a subset of caRNA, thus termed mt-caRNA. In four human cell types analyzed, mt-caRNAs preferentially attach to promoter regions. In human endothelial cells (ECs), the level of mt-caRNA–promoter attachment changes in response to environmental stress that mimics diabetes. Suppression of a non-coding mt-caRNA in ECs attenuates stress-induced nascent RNA transcription from the nuclear genome, including that of critical genes regulating cell adhesion, and abolishes stress-induced monocyte adhesion, a hallmark of dysfunctional ECs. Finally, we report increased nuclear localization of multiple mtRNAs in the ECs of human diabetic donors, suggesting many mtRNA translocate to the nucleus in a cell stress and disease-dependent manner. These data nominate mt-caRNAs as messenger molecules responsible for mitochondrial–nuclear communication and connect the immediate product of mitochondrial transcription with the transcriptional regulation of the nuclear genome.